Evaluasi Surveilans Faktor Risiko Penyakit Tidak Menular (PTM) Berbasis Data Kegiatan “Posbindu PTM” - Ekowati Rahajeng; Mugi Wahidin (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2020)
Abstract Since 2013, Directorate of NCD Prevention and Control has conducted web-based NCD risk factors surveillance with the data source from the ‘Posbindu PTM’ activity. Evaluation of the surveillance should be conducted periodically to assess achievement of objectives and target benefits. However, since the surveillance conducted nationally, there has not been a specific evaluation. This article aimed to obtain information about the utilization and problems in implementing NCD risk factors surveillance based on “Posbindu PTM” data. The research method was carried out through a systematic review of articles related to the implementation of NCD risk factor surveillance based on Posbindu PTM data in 2014 to 2020. The articles were searched using a search engine with keywords NCD surveillance, Posbindu PTM, Posbindu surveillance, in June 2020. There were 12 articles that match the keywords and five articles that meet the criteria. The results of the review showed that the data collection instruments of and technical guideline for surveillance of web-based NCD risk factors can be utilized by surveillance officers. The web information system is considered simple, acceptable, has high sensitivity and stability, and is timely. Automatic data collection, processing and analysis greatly facilitate surveillance. The results of the information system analysis are in accordance with the planning requirement. The results of surveillance are useful for outreach / counseling and for student research. The problems in implementing surveillance are the limited number of trained officers, no operational budget, limited population coverage, lack of infrastructure, interference with internet signals and limited peladens. Officers generally have not interpreted the results and disseminate less because of their limited abilities. The web-based PTM risk factor surveillance based on “Posbindu PTM” activity data can be implemented, but not systematically. Increasing the number and capacity of officers, especially in data interpretation improvement of surveillance facility is necessary to increase the benefits and achievement of the goal of prevention and control of PTM/NCD in the community. Abstrak Sejak tahun 2013, Direktorat Pencegahan dan Pengendalian Penyakit Tidak Menular (P2PTM) menyelenggarakan surveilans faktor risiko PTM berbasis web dengan sumber data kegiatan “Posbindu PTM”. Evaluasi surveilans seharusnya dilakukan secara periodik untuk menilai pencapaian tujuan dan manfaat yang ditargetkan. Namun, semenjak surveilans diselenggarakan secara nasional belum dilakukan evaluasi secara khusus. Artikel ini bertujuan memperoleh informasi tentang pemanfaatan dan permasalahan dalam pelaksanaan surveilans faktor risiko PTM bersumber data Posbindu PTM. Metode penelitian dilakukan melalui tinjauan secara sistematik terhadap artikel terkait pelaksanaan surveilans faktor risiko PTM bersumber data Posbindu PTM pada tahun 2014-2020. Pencarian artikel menggunakan mesin pencari dengan kata kunci surveilans PTM, Posbindu PTM, dan surveilans Posbindu pada Juni 2020. Terdapat 12 artikel yang sesuai kata kunci dan lima artikel yang memenuhi kriteria. Hasil tinjauan menunjukkan instrumen pengumpulan data dan petunjuk teknis surveilans faktor risiko PTM berbasis web dapat dimanfaatkan petugas surveilans dengan baik. Sistem informasi web dinilai sederhana, akseptabel, memiliki sensitivitas serta stabilitas tinggi, dan tepat waktu. Pengumpulan, pengolahan, dan analisis data secara otomatis sangat mempermudah pelaksanaan surveilans. Hasil analisis sistem informasi sudah sesuai kebutuhan perencanaan. Hasil surveilans bermanfaat untuk penyuluhan/ konseling dan untuk penelitian mahasiswa. Permasalahan pelaksanaan surveilans adalah keterbatasan jumlah petugas terlatih, tidak adanya anggaran operasional, keterbatasan cakupan penduduk, kurangnya sarana prasarana, gangguan sinyal internet, dan keterbatasan peladen (server). Petugas umumnya belum menginterpretasikan hasil dan kurang melakukan diseminasi karena keterbatasan kemampuan. Surveilans Faktor Risiko PTM berbasis web bersumber data kegiatan ‘Posbindu PTM’ dapat dilaksanakan, namun belum sistematik. Peningkatan jumlah dan kemampuan petugas, khususnya dalam interpretasi data, peningkatan sarana prasarana surveilans perlu dilakukan untuk meningkatkan manfaat serta pencapaian tujuan pencegahan dan pengendalian PTM di masyarakat.